The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ans.16518
|View full text |Cite
|
Sign up to set email alerts
|

Oncological reasons for performing a complete mesocolic excision: a systematic review and meta‐analysis

Abstract: Background While complete mesocolic excision (CME) has been shown to have an oncological benefit as compared to conventional colonic surgery for colon surgery, this benefit must be weighed up against the risk of major intra‐abdominal complications. This paper aimed to assess the comparative oncological benefits of CME. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidelines, a systematic review of the literature until May 2020 was performed. Comparative studies asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
2
9
0
2
Order By: Relevance
“…29 Other known risk factors for a positive margin include previous radiochemotherapy, T3 tumours, N stage 1-2, APR and high BMI. 30 There were similar percentages of cT3 tumours and cN stage 1-2 in our study, but a higher proportion of preoperative radiation or radiochemotherapy in all groups when comparing with the randomised trials. A higher proportion in our study have undergone APR, though this study included by comparison a smaller proportion of low tumours.…”
Section: Discussionsupporting
confidence: 69%
“…29 Other known risk factors for a positive margin include previous radiochemotherapy, T3 tumours, N stage 1-2, APR and high BMI. 30 There were similar percentages of cT3 tumours and cN stage 1-2 in our study, but a higher proportion of preoperative radiation or radiochemotherapy in all groups when comparing with the randomised trials. A higher proportion in our study have undergone APR, though this study included by comparison a smaller proportion of low tumours.…”
Section: Discussionsupporting
confidence: 69%
“…A recent large meta-analysis (including two randomized trials) demonstrated significantly higher rates of overall complications, particularly major vascular injury, associated with CME/CVL/D3 surgery. 41 In the same analysis, the rate of operative blood loss, operative time, anastomotic leak rate, postoperative ileus, and length of hospital stay were similar.…”
Section: Short Term Outcomesmentioning
confidence: 71%
“…Despite the limited randomized data available for CME surgery for colon cancer, the interest in the procedure is reflected by the fact that there were 13 systematic reviews published on the topic between 2009 and 2020, and at least an additional 9 systematic reviews published in 2021 alone. [35][36][37][38][39][40][41][42][43] Pathological outcomes CME with CVL has been shown to be associated with a greater distance between the tumour and vascular tie, a longer colonic specimen length, a larger mesenteric resectional area and higher lymph node yield. 13,36,43 Although higher lymph node yields have been associated with a survival benefit in patients with clinically positive and negative lymph nodes, [44][45][46][47][48] recent genomic and proteomic data have demonstrated a strong correlation between lymph node yield and immune response, where the survival advantage associated with higher lymph node yields is most likely explained by the induction of an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of CME was to remove the afflicted colon and its accessory lymphovascular supply by preserving the visceral peritoneum. After introduction of this technique, which was inspired by total mesorectal excision in rectal cancer surgery, oncologic results improved [1]. The extent of lymph node dissection in general has become a topic of interest for many colorectal surgeons, since the number of retrieved lymph nodes has significant influence on oncological outcome [2,3].…”
Section: Complete Mesocolic Excision Cme) Is a Surgical Technique In ...mentioning
confidence: 99%